2021
DOI: 10.1021/acs.inorgchem.1c02601
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties and Reactivity Study of [MnV(O)(μ-OR–Lewis Acid)] Cores

Abstract: A mononuclear manganese­(V) oxo complex of a bis­(amidate)­bis­(alkoxide) ligand, (NMe4)­[MnV(HMPAB)­(O)] [2; H4HMPAB = 1,2-bis­(2-hydroxy-2-methylpropanamido)­benzene], was synthesized and structurally characterized. A Mn–Oterm distance of 1.566(4) Å was observed in the solid-state structure of 2, consistent with the MnO formulation. The reaction of redox-inactive metal ions (M n+ = Li+, Ca2+, Mg2+, Y3+, and Sc3+) with 2 resulted in the formation of 2-M n+ species, which were characterized by UV–vis, 1H NMR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…A Δ S ‡ value of −23 and ca. −20 cal K –1 mol –1 has been reported for a HAT reaction between Ru IV O or Mn V O and BNAH, respectively. In the occurrence of a hydride atom transfer pathway, a more negative Δ S ‡ value would be expected because of the formation of a more ordered transition state, as reported for the oxidation of 2-propanol .…”
Section: Resultsmentioning
confidence: 97%
“…A Δ S ‡ value of −23 and ca. −20 cal K –1 mol –1 has been reported for a HAT reaction between Ru IV O or Mn V O and BNAH, respectively. In the occurrence of a hydride atom transfer pathway, a more negative Δ S ‡ value would be expected because of the formation of a more ordered transition state, as reported for the oxidation of 2-propanol .…”
Section: Resultsmentioning
confidence: 97%
“…A crystal structure of a mononuclear manganese­(V)-oxo complex, [(HMPAB)­Mn V (O)] − (H 4 HMPAB = 1,2-bis­(2-hydroxy-2-methylpropanamido)­benzene), revealed that a Mn–O term distance is 1.566(4) Å as shown in Figure . The reaction of [(HMPAB)­Mn V (O)] − with redox-inactive metal ions (M n + = Li + , Ca 2+ , Mg 2+ , Y 3+ , and Sc 3+ ) resulted in the formation of [(HMPAB)­Mn V (O)] − -M n + adducts, which were characterized by UV–vis, 1 H NMR, cyclic voltammetry, and in situ IR spectroscopy . Theoretical calculations suggested that the alkoxide oxygen atoms in the ligand scaffold are the most energetically favorable for coordinating the M n + ion at [(HMPAB)­Mn V (O)] − (Figure ).…”
Section: Metal-oxygen Intermediatesmentioning
confidence: 99%
“…X-ray crystal structure of [(HMPAB)­Mn V (O)] − , showing the binding mode of metal ions (M n + ) confirmed by DFT caculations …”
Section: Metal-oxygen Intermediatesmentioning
confidence: 99%
“…However, those studies are scarce and explored in a limited number of examples. , Recently, we examined the electrocatalytic WO reaction by molecular copper complexes supported by redox-active bis-amidate-bis-alkoxide ligands (L 1 and L 2 ) . We also noted that the ligand system (Chart ) is suitable for stabilizing metastable reaction intermediates for spectroscopic interrogation. In this study, we set out to explore the electrocatalytic WO activity of Co complexes supported by L 1 and L 2 and characterize the reaction intermediates involved in the WO reaction. Here, we report the electrocatalytic WO by molecular Co complexes, [Co­(L 1 )] − ( 1 ) and [Co­(L 2 )] − ( 2 ), in 0.1 M phosphate buffer solution (PBS) at pH 8.0 and in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%